2010
DOI: 10.1002/pi.2801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of depolymerised ethylene vinyl acetate on the mechanical, thermal, chemical and shrinkage properties of cured unsaturated polyester resins

Abstract: Unsaturated polyester resins (UPRs) are versatile compounds. However, their major drawback is the high shrinkage exhibited on curing. An attempt was made to reduce the shrinkage of UPRs without affecting other properties. In the present study a commonly used iso‐reactive UPR was modified by the addition of ethylene–vinyl acetate (EVA; subjected to controlled depolymerisation to obtain samples of various molecular weights), and was cured at room temperature. The peak exotherm temperature and gel time were both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This particular aspect can pose several issues to the application of these materials in AM processes. Shenoy and co-workers [52] reported a study on the effect of the addition of ethylene vinyl acetate (EVA) (partially depolymerized and presenting different degrees of branching) on the mechanical, thermal, chemical and shrinkage properties of UPRs. The authors concluded that the addition of 0.5 % wt EVA (with a high degree of branching) led to an improvement in the flexural and tensile properties, without deleterious effects in the HDT and impact properties.…”
Section: Ways To Tailor and Improve The Properties Of The Ups And Uprsmentioning
confidence: 99%
“…This particular aspect can pose several issues to the application of these materials in AM processes. Shenoy and co-workers [52] reported a study on the effect of the addition of ethylene vinyl acetate (EVA) (partially depolymerized and presenting different degrees of branching) on the mechanical, thermal, chemical and shrinkage properties of UPRs. The authors concluded that the addition of 0.5 % wt EVA (with a high degree of branching) led to an improvement in the flexural and tensile properties, without deleterious effects in the HDT and impact properties.…”
Section: Ways To Tailor and Improve The Properties Of The Ups And Uprsmentioning
confidence: 99%
“…In order to compensate the undesirable curing shrinkage of UPR, low profile additives (LPAs), non‐reactive thermoplastic materials, generally used in this area, show high efficiency in eliminating the curing shrinkage . LPA often requires elevated temperature for successful shrinkage control, while effect of inorganic/organic fillers on the volume shrinkage of resin and mechanical composites is rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it pays attention to improve the properties of UP, including toughening modification, lowering volume shrinkage, and enhancing flame retardancy . Previous studies showed that the properties could be ameliorated by adopting traditional additives like low profile additives, and micro inorganic fillers . However, such enhancement is achieved at the expense of other properties.…”
Section: Introductionmentioning
confidence: 99%